Technology Trap and Poverty Trap in Sub-Saharan Africa - Fofack, Hippolyte (World Bank, Washington, DC, 2012)
Since the industrial revolution, advances in science and technology have continuously accounted for most of the growth and wealth accumulation in leading industrialized economies. In recent years, the contribution of technological progress to growth and welfare improvement has increased even further, especially with the globalization process which has been characterized by exponential growth in exports of manufactured goods. This paper establishes the existence of a technology trap in Sub-Saharan Africa. It shows that the widening income and welfare gap between Sub-Saharan Africa and the rest of world is largely accounted for by the technology trap responsible for the poverty trap. This result is supported by empirical evidence which suggests that if countries in Sub-Saharan Africa were using the same level of technology enjoyed by industrialized countries income levels in Sub-Saharan Africa would be significantly higher. The result is robust, even after controlling for institutional, macroeconomic instability and volatility factors. Consistent with standard one-sector neoclassical growth models, this suggests that uniform convergence to a worldwide technology frontier may lead to income convergence in the spherical space. Overcoming the technology trap in Sub-Saharan Africa may therefore be essential to achieving the Millennium Development Goals and evolving toward global convergence in the process of economic development.